2018
DOI: 10.3389/fneur.2018.00498
|View full text |Cite
|
Sign up to set email alerts
|

Large Vessel Disease Modifies the Relationship Between Kidney Injury and Cerebral Small Vessel Disease

Abstract: Background: Recent studies have shown that renal disease is associated with magnetic resonance imaging (MRI) markers of cerebral small vessel disease (CSVD), independent of traditional vascular risk factors. Although large artery lesions might be involved in the cerebrorenal association, evidence has been lacking.Methods: A total of 928 participants from a population-based cohort study were included. Kidney injury measurements included urinary albumin-to-creatinine ratio (ACR) and estimated glomerular filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…These results are in agreement with study published in 2018 by Ao et al who included 928 participants and found a relation between large artery atherosclerosis and cerebral SVD [14]. Another study done by Nam and his Because cerebral SVD is diffuse and affects the small arteries, arterioles, capillaries and venules, the impairment of cerebral and extracerebral [19] autoregulation is global [20].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with study published in 2018 by Ao et al who included 928 participants and found a relation between large artery atherosclerosis and cerebral SVD [14]. Another study done by Nam and his Because cerebral SVD is diffuse and affects the small arteries, arterioles, capillaries and venules, the impairment of cerebral and extracerebral [19] autoregulation is global [20].…”
Section: Discussionsupporting
confidence: 91%
“…Abstract screening and exclusion of nonoriginal research, records lacking full text, or records that did not quantitatively assess a relationship between arterial stiffness and cSVD resulted in 82 publications for systematic review. Of the 82 articles, 12 assessed recent small subcortical infarcts, 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 24 assessed the presence of lacunes, 21 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 9 assessed enlarged perivascular spaces, 118 , 138 , 144 , 145 , 150 , 152 , 153 , 154 , 155 23 assessed cerebral microbleeds, 37 , 118 , 120 , …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included in the systematic review were cross‐sectional in nature; with 86% of the cross‐sectional studies reporting a significant association between arterial stiffness and cSVD. 21 , 118 , 119 , 120 , 121 , 123 , 124 , 125 , 126 , 127 , 128 , 130 , 131 , 132 , 133 , 134 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 147 , 148 , 150 , 151 , 152 , 153 , 154 , 156 , 157 , 158 , 160 , 161 , 163 , 165 , 166 , 167 , 169 , 171 , 172 , 173 , 176 , 177 , 178 , 179 , 182 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we also observed preserved renal function in MSC-infused animals. Due to low vascular resistance in the kidney, the arterioles are highly susceptible to the endothelial injury of small vessels [ 36 , 37 ], which is often associated with a high prevalence of chronic kidney disease and poor prognosis among the elderly population [ 36 , 38 , 39 , 40 ]. In this study, the concentrations of serum BUN and Cre were elevated in the vehicle-infused group compared to those in the control group, which was also observed in other previous studies [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%